PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN LEMBAR KERJA PESERTA DIDIK (LKPD) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI MATERI MATRIKS - Susanti Jayaningrat; Achmad Buchori; Nika Dewi Indriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This article is a research method that aims to determine the extent of improving communication skills with the use of the Problem Based Learning (PBL) model on the mathematical communication skills of grade XI BO 1 SMK N 6 Semarang students on matrix material using the Problem Based Learning (PBL) learning model. The subjects of this study were 33 students of class XI BO 1. The research method used in this study is research. The research method used in this study is class action research (PTK). This research was carried out in two cycles. The instrument used is a test instrument in the form of 3 questions describing matrix material, and each question refers to indicators mathematiical Communication. Data analysis techniques use descriptive analysis techniques. The results of this study show that students' mathematical communication skills by applying the LKPD-assisted Problem Based Learning model have increased in each cycle. In cycle 1 the average value is 79, while cycle 2 has increased the average value to 91. The classical completeness rate increased from 67% in cycle 1 to 91% in cycle 2.